Modification of Polylactic Acid with Eggshell Filler as Biodegradable Composite - Sambudi, Nonni Soraya; Radini, Fitri Ayu; Ahmad Kamal, Norashikin; Jusoh, Norwahyu (Journal of Engineering and Technological Sciences, 2025)
In this study, polylactic acid (PLA) was proposed as a material for producing bioplastics due to the desirable properties, including high processability, low cost, and good transparency. However, the degradation of PLA as a bioplastic remains a significant challenge. To address this problem, PLA was modified by blending with a bio-filler, in the form of calcium carbonate (CaCO3) prepared from eggshell powder (ESP). The CaCO3 filler in form of ESP was incorporated into PLA using the solution casting method. The parameter being varied was the ESP loading, ranging from 0 wt% to 20 wt%. The results showed that the inclusion of eggshell-derived filler in PLA increased tensile strength and Young’s modulus by 10%, from 24.12 to 26.61 MPa, and 162%, from 3022 to 7932 MPa, respectively. The degradability of composite was done through burial test, which the weight of PLA/ESP-20wt% was decreased by 11.11 wt% after 3 weeks. This suggests that eggshell waste has the potential to serve as an effective filler to improve the mechanical strength and degradation of PLA.